2022
DOI: 10.3389/fpubh.2021.774675
|View full text |Cite
|
Sign up to set email alerts
|

How Has the Nationwide Public Health Emergency of the COVID-19 Pandemic Affected Older Chinese Adults' Health Literacy, Health Behaviors and Practices, and Social Connectedness? Qualitative Evidence From Urban China

Abstract: Older Chinese adults' daily lives have been affected significantly during the outbreak phase of the COVID-19 pandemic since January 2020. They were confronted with activity restrictions due to strict pandemic prevention. The older population also had to get accustomed to widely-used modern technologies in community management, such as health codes and WeChat groups. By late 2021, mainland China had reduced the prevalence of COVID-19, and people's daily lives had primarily returned to pre-pandemic normality. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Age could be a reason for the difference, as younger MSM may perceive higher mpox infection risk due to sexual activeness 27 and have a better understanding of the importance of both measures to halt transmission, which strengthens their intention to adopt preventive measures 34 . Additionally, frequent quarantine during the COVID‐19 pandemic in China may have raised Chinese YMSM's health literacy about the control of infectious diseases and acceptance of self‐isolation and disclosure 35 . Moreover, the existence of social desirability bias may also contribute to the difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age could be a reason for the difference, as younger MSM may perceive higher mpox infection risk due to sexual activeness 27 and have a better understanding of the importance of both measures to halt transmission, which strengthens their intention to adopt preventive measures 34 . Additionally, frequent quarantine during the COVID‐19 pandemic in China may have raised Chinese YMSM's health literacy about the control of infectious diseases and acceptance of self‐isolation and disclosure 35 . Moreover, the existence of social desirability bias may also contribute to the difference.…”
Section: Discussionmentioning
confidence: 99%
“…34 Additionally, frequent quarantine during the COVID-19 pandemic in China may have raised Chinese YMSM's health literacy about the control of infectious diseases and acceptance of self-isolation and disclosure. 35 Moreover, the existence of social desirability bias may also contribute to the difference. The finding suggests promoting self-isolation and informing close contacts as a mpox outbreak response is feasible among YMSM.…”
Section: Factors Associated With the Behavioral Intention Of Self-iso...mentioning
confidence: 99%
“…Supposing that it is because alcohol drinking provides older adults with opportunities to participate in social activities for better social engagement [ 53 , 64 ], in that case, communities can work more on this to increase older Canadians’ social engagement [ 65 ]. Plenty of health-benefiting techniques work efficiently to help them avoid isolation, such as establishing social connections sites [ 66 ] and promoting the application of information and communication technologies [ 67 , 68 ], especially under the ongoing COVID-19 pandemic [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smartphone ownership among seniors (65 and older) is 30%, compared to 86% among those aged 18 to 29 [ 3 ]. While being isolated from social life had little negative impact on young people during the spread of COVID-19, the isolation experienced by the older population has become more pronounced due to a lack of infrastructure in smart devices suitable for the elderly population, aggravating their physical and psychological problems [ 4 , 5 , 6 , 7 ]. One study found that older people who use mobile internet are 33.1 percent less lonely than those who do not [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%